Pressure promotes DNA synthesis in rat cultured vascular smooth muscle cells. - Hishikawa, K (1994)
High blood pressure is one of the major risk factors for atherosclerosis. In this study, we examined the effects of pressure on cell proliferation and DNA synthesis in cultured rat vascular smooth muscle cells. Pressure without shear stress and stretch promotes cell proliferation and DNA synthesis in a pressure-dependent manner. Pressure-induced DNA synthesis was inhibited significantly by the phospholipase C (PLC) inhibitor 2-nitro-4-carboxyphenyl-N,N-diphenylcarbamate, the protein kinase C inhibitor H-7, 1-(5-isoquinolinylsulfonyl)-2-methyl-piperazine, staurosporine, and the tyrosine kinase inhibitor ([3,4,5-trihydroxyphenyl]methylene)propanedinitrile. To clarify whether activation of PLC and calcium mobilization are involved in pressure-induced DNA synthesis, production of 1,4,5-inositol trisphosphate (IP3) and intracellular Ca2+ was measured. Pure pressure increased IP3 and intracellular Ca2+ in a pressure-dependent manner. The increases in both IP3 and intracellular Ca2+ were inhibited significantly by 2-nitro-4-carboxyphenyl-N,N-diphenylcarbamate. This study demonstrates a novel cellular mechanism whereby pressure regulates DNA synthesis in vascular smooth muscle cells, possibly via activation of PLC and protein kinase C.